siRNA-Mediated Silencing of doublesex during Female Development of the Dengue Vector Mosquito Aedes aegypti. - Keshava Mysore; Longhua Sun; Michael Tomchaney; Gwyneth Sullivan; Haley Adams; Andres S Piscoya; David W Severson; Zainulabeuddin Syed; Molly Duman-Scheel (Public Library of Science (PLoS), 2015)
The development of sex-specific traits, including the female-specific ability to bite humans and vector disease, is critical for vector mosquito reproduction and pathogen transmission. Doublesex (Dsx), a terminal transcription factor in the sex determination pathway, is known to regulate sex-specific gene expression during development of the dengue fever vector mosquito Aedes aegypti. Here, the effects of developmental siRNA-mediated dsx silencing were assessed in adult females. Targeting of dsx during A. aegypti development resulted in decreased female wing size, a correlate for body size, which is typically larger in females. siRNA-mediated targeting of dsx also resulted in decreased length of the adult female proboscis. Although dsx silencing did not impact female membrane blood feeding or mating behavior in the laboratory, decreased fecundity and fertility correlated with decreased ovary length, ovariole length, and ovariole number in dsx knockdown females. Dsx silencing also resulted in disruption of olfactory system development, as evidenced by reduced length of the female antenna and maxillary palp and the sensilla present on these structures, as well as disrupted odorant receptor expression. Female lifespan, a critical component of the ability of A. aegypti to transmit pathogens, was also significantly reduced in adult females following developmental targeting of dsx. The results of this investigation demonstrate that silencing of dsx during A. aegypti development disrupts multiple sex-specific morphological, physiological, and behavioral traits of adult females, a number of which are directly or indirectly linked to mosquito reproduction and pathogen transmission. Moreover, the olfactory phenotypes observed connect Dsx to development of the olfactory system, suggesting that A. aegypti will be an excellent system in which to further assess the developmental genetics of sex-specific chemosensation.